FORMULASI NANOEKAPSULASI EKSTRAK DAUN KELOR (Moringa oleifera) /KITOSAN-NATRIUM TRIPOLIPOSFAT (NaTPP) - Vivi Purwandari; Isnaeni Isnaeni; Rizka Rahmi; Ahmad Zukhruf Akbari; Muhammad Zaim Akbari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2022)
Moringa (Moringa oliefera) contains several antioxidant compounds such as quercetin and chlorogenic acid. However, antioxidants have weaknesses, namely that they are easily damaged by exposure to oxygen, light, high temperatures, and drying. One way to maintain and increase the stability of antioxidants is by encapsulation. The purpose of this study was to determine the optimum formulation of quercetin nanoencapsulation of moringa leaf extract using chitosan and sodium tripolyphosphate (Na-TPP) using the ultrasonication method. Moringa leaf extract was obtained by repeated ultrasonication 1x 15, 3x15, and 5x15 minutes, frequency 24 kHz, and using alcohol 96%. The encapsulation process was carried out with three variable ratios of the amount of chitosan: Na-TPP added to 10 mL of Moringa leaf extract solution (F0), namely 5:1 (F1), 2:1 (F2), and 1:1 (F3). Test results for flavonoids as quercetin using a UV-Vis spectrophotometer showed that the Quercetin content in Moringa leaf extract ultrasonicated 5x15 minutes was 12.146%, the characterization of the Particle Size Analyzer (PSA) showed encapsulated particle sizes of 170.3 and 209.7 nm with polydisperse index <0 .5, the antioxidant activity test using the DPPH method showed that F0 was 61.4% and F2 had the highest antioxidant activity, namely 81.2%. Analysis of the morphology of nanoparticles using Scanning Electron Microscopy (SEM) showed that the particles were spherically distributed evenly. Nanoencapsulation of Moringa leaf extract has resulted and an increase in the antioxidant activity of Moringa leaf extract after encapsulation using Chitosan-NaTPP, from 61.4% to 81.2% (F2).